Action Research for community business development. Issue 1 (2014) - ,
Abstract : Purpose – The purpose of this paper is to introduce the idea of Action Research as a way of making academic research more relevant for social economic change.Design/methodology/approach – This paper seeks a middle path by presenting a method for Action Research that is both scientific and that results in practical social‐economic impact on a local society. The method is divided into 11 systematic steps.Findings – The author has found that the method results in job creation and place‐based economic development.Originality/value – Usually social activists and academic professionals do not mix. This approach combines both theory and practice, which is unusual in university circles.